Coalbed methane reservoir dynamic simulation comparisons using the actual steeply inclined model and ideal steeply inclined model - Qin, Quanling; Li, Xin; Peng, Rendong; Peng, Shiqi; Liu, Yipan; Zhou, Xiang; Yang, Jingwen (Frontiers in Earth Science, 2022)
Numerical simulation is an efficient method to quantitatively describe the reservoir dynamics of coalbed methane (CBM) reservoirs. The ideal steeply inclined model (ISIM), assumed to be a steeply inclined plate, has been widely applied in steep coalbed methane reservoir modeling, although the ISIM cannot accurately reflect the actual reservoir geological conditions. In this paper, the dynamics of CBM production and reservoirs using the ISIM and actual steeply inclined model (ASIM) were compared, taking the steep coal in the Fukang mining area located in northwestern China as an example, with the purpose of revealing the differences and applicability of the ASIM and ISIM. The ASIM and ISIM were established by Petrel software, and CBM production was matched and predicted by Eclipse software. Data reflecting reservoir dynamics, such as water saturation, reservoir pressure, and gas content, were extracted. The dynamic changes in the reservoir physical properties of the ASIM and ISIM were also compared. The results showed that: (1) multiple gas production peaks occurred in both ASIM and ISIM. The maximum daily gas production of ASIM occurred earlier than the maximum daily gas production of ISIM. The peak gas production and cumulative gas production of ASIM were both greater than the peak gas production and cumulative gas production of ISIM. (2) Due to the variations in grid shape and dip angle with each grid in the ASIM, the production effect of the ASIM was better than the production effect of the ISIM in the third stage (4-10 years) of drainage. (3) In the third stage (4-10 years) of drainage, the decrease rate of reservoir pressure of ASIM was larger than the decrease rate of reservoir pressure of ISIM because of the relatively better production performance of ASIM. (4) Differentiation of gas and water dominated the variation trend of gas content, and in the third stage (4-10 years) of drainage, the ASIM has higher recovery efficiency compared with ISIM. Compared with ISIM proposed by previous scholars, the ASIM was more helpful to monitor the dynamic behavior of coal reservoirs, and ASIM can provide a more reliable basis for guiding coalbed methane development.